The Role of Humanistic Education Management in Improving the Quality of Social Intervention in Community Service - Hanif, Muh.; Suherlan; Ausat, Abu Muna Almaududi (PT. LITERASI SAINS NUSANTARA, 2025)
This research aims to examine the role of humanistic education management in improving the quality of social intervention in community service activities. The humanistic approach in education places humans as active subjects in the learning process and social empowerment, so that values such as empathy, respect for individual dignity, and dialogue become the main foundation in designing social intervention programs. This research uses a literature review method with a qualitative approach and descriptive analysis. Data were collected from Google Scholar and other credible scientific sites in the period 1951-2025. Of the 30 articles reviewed, 18 were selected through a rigorous selection based on the relevance and quality of the sources. The results showed that educational management based on humanistic principles has been proven to increase the effectiveness, sustainability, and community acceptance of social interventions conducted by universities. This study recommends the importance of integrating humanistic values into the management system of community service programmes in order to produce more meaningful and transformative social impacts.